GROWTH RESPONSE OF RABBITS TO RUMEN LIQUOR–FERMENTED SUGAR BY-PRODUCT MEAL DIETS WITH MULTIGRAIN ENZYME SUPPLEMENTATION (FULafia Journal of Science and Technology, 2026)
The global demand for animal protein necessitates the exploration of sustainable feed alternatives in livestock production. Rabbit farming is considered a promising avenue due to the high reproductive rate and their ability to thrive on diverse feedstuffs. This study investigated effect of rumen-liquor fermented solid waste product of sugar industry (FSWAPSI) supplemented with enzyme on the performance of rabbits. The experiment used 72 weaner rabbits assigned to a 3x2 factorial arrangement fitted into Completely Randomized Design and replicated four times with 3 rabbits each. Six diets were formulated to be isonitrogenous and iso-caloric, supplementing FSWAPSI at 20, 30, and 40 % for weaners and 40, 50 and 60 % for growers, with enzyme supplementation at 0 and 200 ppm. Rumen liquor was used to inoculate SWAPSI and fermented before sun-drying. In the grower phase the result shows that higher level of the test ingredient was tolerated, 20 % FSWAPSI inclusion group showed a significant (P
Keywords: Rabbit; rumen-liquor; fermentation; sugar industry waste; enzyme supplementation; growth performance